2013
DOI: 10.1017/s0021859613000117
|View full text |Cite
|
Sign up to set email alerts
|

Variability in glutenin subunit composition of Mediterranean durum wheat germplasm and its relationship with gluten strength

Abstract: SUMMARYThe allelic composition at five glutenin loci was assessed by one-dimensional sodium dodecyl sulphate polyacrylamide gel electrophoresis (1D SDS–PAGE) on a set of 155 landraces (from 21 Mediterranean countries) and 18 representative modern varieties. Gluten strength was determined by SDS-sedimentation on samples grown under rainfed conditions during 3 years in north-eastern Spain. One hundred and fourteen alleles/banding patterns were identified (25 at Glu-1 and 89 at Glu-2/Glu-3 loci); 0·85 of them wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
55
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 24 publications
18
55
2
5
Order By: Relevance
“…Previous research conducted with the same collection revealed that it properly represents the diversity of durum wheat landraces in the Mediterranean Basin for yield, quality attributes (Nazco et al 2012), glutenin alleles (Nazco et al 2013), and allelic combinations at Glu-1/Glu-3 loci (Nazco et al 2014). Our results revealed a significant effect of the climatic zone origin on the number of days the landraces needed to reach the main growth stages.…”
Section: Discussionsupporting
confidence: 57%
“…Previous research conducted with the same collection revealed that it properly represents the diversity of durum wheat landraces in the Mediterranean Basin for yield, quality attributes (Nazco et al 2012), glutenin alleles (Nazco et al 2013), and allelic combinations at Glu-1/Glu-3 loci (Nazco et al 2014). Our results revealed a significant effect of the climatic zone origin on the number of days the landraces needed to reach the main growth stages.…”
Section: Discussionsupporting
confidence: 57%
“…A total number of 114 individual banding patterns, potentially Glu-1/Glu-3/Glu-2 allele-specific, were identified in the collection, with the following distribution: 5 and 20 HMW-GS encoded by the Glu-A1 and Glu-B1 loci respectively, and 15, 72 and 2 LMW-GS encoded by the Glu-A3, Glu-B3 and Glu-B2 loci, respectively (Nazco et al 2013). Considering jointly both glutenin groups (HMW-GS and LMW-GS), a total of 131 combinations were detected in the whole collection, with 126 identified in LR and 9 in MC.…”
Section: Resultsmentioning
confidence: 99%
“…The 32 combinations found at HMW-GS loci were based on the joint expression of 5 and 20 allelic variants at Glu-A1 and Glu-B1 loci, respectively, while the 98 combinations detected at LMW-GS loci were related to the expression of 15 alleles or production of banding patterns at Glu-A3 locus, 72 at Glu-B3 and 2 at Glu-B2 (Nazco et al 2013). This diversity is substantially greater than reported by previous studies conducted in durum wheat (Turchetta et al 1995;Cherdouh et al 2005;Moragues et al 2006c).…”
Section: Discussionmentioning
confidence: 96%
“…In cultivars from both countries the null allele, common in old and in a few intermediate cultivars, was replaced by band 6 (Glu-A3a) in the modern cultivars. Band 6 has been found to be the most frequent both in landraces and modern cultivars (Nieto-Taladriz et al 1997;Carrillo et al 2000;Moragues et al 2006;Nazco et al 2013). The two modern Spanish cultivars carrying subunit 6+11 at Glu-A3 had good gluten strength, but this result could not be attributed to this band exclusively, rather it is more likely due to the interaction with the alleles present at other loci.…”
Section: Changes In Glutenin Allelic Composition and Its Effects On Gmentioning
confidence: 98%
“…The null allele has been found in very high frequencies in other durum collections (Vallega 1988;Branlard et al 1989;Nazco et al 2013), and it has been found practically fixed in modern germplasm worldwide. Despite studies reporting the positive effect on durum wheat quality of allele 1 at the Glu-A1 locus (Martínez et al 2005), the two old cultivars carrying it in this study had weak gluten.…”
Section: Changes In Glutenin Allelic Composition and Its Effects On Gmentioning
confidence: 99%